A Rare Ocular Anomaly of Congenital Bilateral Aphakia in a Goat Kid - A Case Report - Kumaran, M Senthil; Senthamizhan, S; Vishnugurubaran, D; Vijayakaran, K; Arunmozhi, N; Vijayarajan, A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Ocular defects in food-producing livestock have a significant impact on the economy of the rearing community. Every year there is an increase in the number of food-producing animals and reports of congenital anomalies become evident in the total number of animals affected per year (Williams, 2010). Reports on ocular anomalies in ruminants that too in the eyes of sheep and goats are very limited (Sangamwar et al., 1997). Aphakia means absence of lens. Congenital aphakia is an exceptionally rare anomaly that is reported only in very few livestock. This anomaly is either due to the failed induction of lens placode or due to the resorption or expulsion of the lens in utero after normal development (Gelatt and Plummer, 2022). Aphakia is commonly associated with anterior segment dysgenesis. The diagnosis can be done with slit lamp biomicroscopy, retinoscopy and ultrasonography. Enucleation is one of the choices of treatment in livestock (Sato et al., 2017).